MO349: Occurrence of Postoperative Acute Kidney Injury (AKI) in One Lung Ventilated Patients. (3rd May 2022) - Jovanovsi- Srceva, Marija; Nikolov, Igor; Nikolova, Dushanka; Gavrilovska, Aleksandra; Kuzmanovska, Biljana; Gjorgjievski, Nikola; Dzekova-Vidimliski, Pavlina; Severova- Andreevska, Galina; Rambabova- Bushljetik, Irena; Kuzmanovski, Igor; Jakupi, Nexhati
Abstract: BACKGROUND AND AIMS: During lung surgery, preoperative fluids are given in restrict manner. This is in correspondence with the fact that lungs produce polyphasic injury during surgery and increased levels of different inflammation, traumatic and stress markers, on one side and a lack of fluids that complicate the transfer of water and kidney function on the other side [1 ]. One lung ventilation additionally complicate ventilation/perfusion ratio in the lungs, has overall impact on the whole body and to novel knowledge it indirectly leads to kidneys hypoperfusion and injurie [2 ]. The aim of our study is to evaluate the level of postoperative acute kidney injurie (AKI) occurrence in patients who underwent OLV. METHOD: In prospective study, 60 patients that underwent lung resection in OLV, BMI<30 m 2 without hepatic or renal endocrine diseases, aged 45–65 at the University Clinic for thoracic surgery in Skopje were included. Patients who underwent prior haemotherapy or radiotherapy were exuded. In all patients, we evaluate the demographic, clinical, preoperative state, duration of OLV, operation data and fluid assessment. Primary, we evaluate the occurrence and staging of AKI according to KDGIO criteria [3, 4 ]. A total of 72 h postoperatively in all patients and post hoc, we corelate its occurrence to several factors. RESULTS: On average, patients were 59.7 +5.9 SD years old. More males were operated (80%). Overall, AKI stage 1 occurred in total of 13.3% (8 patients), AKI stage 22 in 3.3% (2 patients) and AKI stage 3 in 1.6% (1 patient). OLV longer than 60 min was in 85% of the patients, and all stages AKI were after this time duration. Lobectomy was done in 65% of the patients, while pulmectomy in 18.3% and bilobectomy in 16.7%. In relation to type of surgery done most of the patients that had pneumectomy had AKI 1 (27.2%), and additionally, only in this analysed surgery group, AKI 3 occurred in 9%. In correspondence to the side operated, right side was operated in 57.7% of the patients, and most of the AKI occurred in the right-sided surgery. Most of the patients who developed AKI preoperatively had hypertension and other cardiovascular issues. CONCLUSION: AKI occurs significantly after OLV, in relation to the type of surgery. Mainly when right-side surgery is done. However, more severe AKI occurs when pulmectomy is done. Fluid regiment, OLV longer than 60 min and some preoperative cardiovascular diseases may contribute to its occurrence.